Pedagogical Innovations in Language Teaching Methodologies - Wisran Wisran (Jurnal Pendidikan Refleksi, 2022)
Language teachers have always been concerned about the inadequacy of conventional methods of language teaching in education systems. As a result, the language teaching pendulum is swinging from methods to post-method pedagogy, although it still remains in motion. The dual focus on both socio-cultural theories to second language acquisition (SLA) and improvements in technologies wins the attention of practitioners, curriculum designers, and students as the major stake holders in applied linguistics. This has resulted in greater emphasis on the important role of techniques and technologies in language teaching. Many have tried to find a more innovative direction in this respect (Rodgers, 2000). This article, along with reviewing different predictions made in this direction, takes a more sociocultural technological perspective to address the potentially important issues in language teaching in future.